2019
DOI: 10.1096/fj.201802650rr
|View full text |Cite
|
Sign up to set email alerts
|

Primary endothelial cell–specific regulation of hypoxia‐inducible factor (HIF)‐1 and HIF‐2 and their target gene expression profiles during hypoxia

Abstract: During hypoxia, a cellular adaptive response activates hypoxia‐inducible factors (HIFs; HIF‐1 and HIF‐2) that respond to low tissue‐oxygen levels and induce the expression of a number of genes that promote angiogenesis, energy metabolism, and cell survival. HIF‐1 and HIF‐2 regulate endothelial cell (EC) adaptation by activating genesignaling cascades that promote endothelial migration, growth, and differentiation. An HIF‐1 to HIF‐2 transition or switch governs this process from acute to prolonged hypoxia. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
120
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(154 citation statements)
references
References 69 publications
20
120
0
3
Order By: Relevance
“…HIF1α levels peaked between 4 and 8 hrs of hypoxia exposure (Fig 1A), consistent with previous observations in microvascular endothelial cells (44). The mRNA expression of HIF1α target genes, vascular endothelial growth factor (VEGF), solute carrier family 2 member 1 (SLC2A1, which encodes glucose transporter 1 (GLUT1)), pyruvate kinase 2 (PKM2), N-myc downstream regulated 1 (NDRG1), and carbonic anhydrase 9 (CA9), also increased in response to hypoxia (Fig 1B) (44,45). As expected, the proliferation of HMEC-1 cells was significantly reduced in hypoxia compared to cells grown under normoxic conditions (S1 Fig A).…”
Section: Resultssupporting
confidence: 92%
“…HIF1α levels peaked between 4 and 8 hrs of hypoxia exposure (Fig 1A), consistent with previous observations in microvascular endothelial cells (44). The mRNA expression of HIF1α target genes, vascular endothelial growth factor (VEGF), solute carrier family 2 member 1 (SLC2A1, which encodes glucose transporter 1 (GLUT1)), pyruvate kinase 2 (PKM2), N-myc downstream regulated 1 (NDRG1), and carbonic anhydrase 9 (CA9), also increased in response to hypoxia (Fig 1B) (44,45). As expected, the proliferation of HMEC-1 cells was significantly reduced in hypoxia compared to cells grown under normoxic conditions (S1 Fig A).…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, HIF-3α2 enrichment is not observed at the single HRE required for HIF-2 driven EPO regulation at the liver inducibility element immediately 3′ to EPO [17]. This may imply that HIF-3 does not compete for the binding sites used by HIF-1 and HIF-2 as was recently shown to be true between HIF-1 and HIF-2 despite a set of shared target genes [15,40]. Finally, using the HIST1H2BK gene, we show that HIF-3 may redistribute to non-endogenous HREs upon overexpression and that chromatin occupancy studies should be paired with functional assays to dissect endogenous target genes.…”
Section: Discussionmentioning
confidence: 96%
“…MVEC are key regulators of organ homeostasis, and control perfusion and permeability locally to match organ demand (Augustin and Koh, 2017;. Perception and response to oscillations in oxygen availability, whether as a result of changes in tissue need or environmental supply, are essential aspects of MVEC function (Bartoszewski et al, 2019). In this study, primary MVEC from two continuous endothelial capillary networks were isolated from brain and lung tissue, and their responses to hypoxia compared.…”
Section: Discussionmentioning
confidence: 99%
“…As known key mediators of hypoxia response, activation of the two main HIF-a isoforms was assessed in both MVEC populations, to investigate if discrepancies in the HIF-signalling pathway corresponded to differences in cell viability. HIF-1a expression showed the canonical transient upregulation in both lung and brain MVEC (Bartoszewski et al, 2019;Uchida et al, 2004), although consistently higher levels of this isoform was found in cells from the lung, at all time points ( Figure 1C). HIF-2a protein levels decreased only at later time points for lMVEC, but bMVEC showed strikingly higher levels of HIF-2a protein throughout the hypoxia time course ( Figure 1D).…”
Section: Brain and Lung Microvascular Endothelial Cells Respond Diffementioning
confidence: 92%